Inflammatory Bowel Disease and Gut Microbiota Dysbiosis: Current understanding and Future Direction - Verma, Ritu; Shiva, Km.; Singh, Ranveer; Sherawat, Kajal; ., Simran; Bhardwaj, Poonam (Journal of Biomedical and Pharmaceutical Research, 2024)
Inflammatory Bowel Disease (IBD) represents a group of chronic, relapsing inflammatory disorders primarily affecting the gastrointestinal tract. The pathogenesis of IBD is multifaceted, involving genetic predisposition, environmental triggers, and dysregulation of the immune response. Recent research has illuminated the pivotal role of gut microbiota dysbiosis in the development and perpetuation of IBD. The human gut harbors a complex and dynamic ecosystem of microorganisms that profoundly influences host health and disease. Alterations in the composition, diversity, and function of the gut microbiota, termed dysbiosis, have been consistently linked to IBD. Shifts in microbial composition, reduction in microbial diversity, and imbalances in beneficial versus pathogenic microorganisms characterize the dysbiotic state associated with IBD.The intricate interplay between the host immune system and the gut microbiota is a key determinant in IBD pathogenesis. Dysbiosis triggers aberrant immune responses, leading to chronic mucosal inflammation and tissue damage. Furthermore, dysbiotic alterations disrupt essential microbial-derived metabolites and signaling molecules crucial for gut homeostasis, further exacerbating the disease. Advancements in high-throughput sequencing technologies and metagenomic analysis have enabled comprehensive characterization of microbial communities in IBD, uncovering microbial signatures and functional pathways associated with disease phenotypes and treatment responses. Therapeutic interventions targeting the gut microbiota, such as probiotics, prebiotics, fecal microbiota transplantation, and microbial-based therapies, have shown promise in preclinical and clinical studies for modulating dysbiosis and ameliorating IBD symptoms. Keywords: Inflammatory Bowel Disease, Dysbiosis, Fecal microbiota, Probiotics